PENGARUH NILAI PERUSAHAAN, KESEMPATAN BERTUMBUH PERUSAHAAN DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM DIMASA YANG AKAN DATANG - Seto Makmur Wibowo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
This study aims to analyze the iqfluence offirm value, the opportunity to grow the company and future operating cash flow to future stock return. The population of this study is manufacturing companies listed in Indonesia Stock Exchange. The samples used were 23 companies which include consumer goods industry which published a report in 2009-2012. The results of this study using multiple regression showed that the firm value and operating cash flow has no effect on Future Stock Return. But the company's growth opportunity has a positive and significant impact on Future Stock Return